ADB support for school education (K-12) in Asia and the Pacific. - Tulivuori, Jukka (Economics working papers.)
ADB has been working for more than 50 years in Asia and the Pacific to expand and improve education at all levels and has allocated about 15 billion in loans and grants to the sector. The brief provides examples of ADB support to improve education quality and relevance, systems and governance, and equitable access. It also identifies emerging priority areas such as supporting developing member countries to update curricula, improve teacher quality, promote the use of technology, and mobilize more financial resources.